History of Bangladesh, 1704-1971 : vol 2- economic history - Islam, Sirajul. 1939-; Harun-or-Rashid, 1954-; Asiatic Society of Bangladesh (Dhaka, Bangladesh : Asiatic Society of Bangladesh, 1992)
Contributed articles.
v. 1. Political history -- v. 2. Economic history -- v. 3. Social and cultural history.
Includes bibliographical references and indexes.
Keywords: Bangladesh -- History; Bengal (India) -- History